Construction and validation of indicators to evaluate the implementation of the kangaroo method using the Delphi technique - Cândido, Joice Luiza Alves; Frias, Paulo Germano de; Sarinho, Silvia Wanick (Revista de Enfermagem da UFPI, 2023)
Objective: To present the validation process of a matrix of indicators to evaluate the implementation of the second and third stages of the Kangaroo Method (KM) in two reference maternity hospitals and in primary care in Recife. Methods: The construction and validation process followed four stages: (1) elaboration of the logical model of the 2nd and 3rd stage of the KM; (2) composition of the preliminary indicator matrix; (3) selection of experts, sending indicators to this group for analysis using the Delphi Technique; (4) consolidation of results and sending to experts for second consultation and final analysis. A Content Validity Index (CVI) equal to or greater than 80% was adopted to establish agreement. Results: The logical model was composed of components for the 2nd and 3rd stages of the KM, with the Education and Care subcomponents, and a component for the interface of the two stages, with the Management subcomponent. Of the 110 items presented, two did not present consensus in the first round and three suggestions for changes were made. Five new indicators were included, totaling 113 indicators at the end. Conclusion: The use of the Delhi technique made it possible to expand the consensus and validate the KM...